Implementasi Kebijakan Pemerintah Kota terhadap Standarisasi Pendirian Condominium Hotel di Kota Denpasar - Drupadi, Anak Agung Intan; Dewi Pascarani, Ni Nyoman; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2015)
ABSTRACT Â  Tourism development in the island of Bali is currently experiencing a rapid increase. Denpasar as the capitalcity of Bali becomes a barometer of the progress of tourism and also the central area of ??tourism development. The increasing number of tourists visiting Bali would require the availability of tourism accommodation. Condotel is alodging that has facilities like star-hotels. Currently condotelshave been a long-term investment for investors, because this condotel rooms can be put into a transaction. The rapid development in Denpasar condotels gives adverse impactsto the environment, so that in this case the Denpasar municipality government issued a regulation relating to the establishment of condotelestablishment standardization to overcome the negative impact on the surrounding environment. The aim of this study was to investigate the implementation of the Mayor Regulations relating to condotel establishment standardization in Denpasar. This study used descriptive qualitative method. Results from this study in the application of regulations issued by Denpasar municipality government related to the implementation of the standardization of condotelestablishment wererunning less effectively. The lack of effective implementation of the standardization of condotel establishment was caused by several factors, namely: 1. Unclear communication between the parties involved in the establishment of condotels. 2. Lack of adequate human resources in order to act as an implementer of policy regulations issued by the government relating to the standardization of condotel establishment. 3. The disposition or temperament, characteristics of implementing policies that were less concerned with the policy procedures that had been issued. 4. Lack of special specifications associated with bureaucratic structures and also SOPs that could support the implementation of the standardization of condotelestablishment. Â  Keywords: Condotel, City Government Policies, Establishment Standards, Implementation